Fluid-Fluid Level Formation: A Rare Finding of Extracranial Head and Neck Schwannomas - Kato, H.; Kanematsu, M.; Mizuta, K.; Aoki, M.; Yamada, K.; Yamakawa, H.; Iwama, T.; Hirose, Y. (American Journal of Neuroradiology, 2009)
SUMMARY: We present 3 cases of extracranial head and neck schwannomas exhibiting fluid-fluid levels. In the described cases, CT and MR imaging showed predominantly cystic components, intermixed with cellular components. Histopathologic examinations of excised specimens revealed hemosiderin deposition, reflecting intratumoral hemorrhages, which was presumably a cause of fluid-fluid levels. Although fluid-fluid levels are nonspecific findings, schwannoma should be considered when radiologic images demonstrate marked cystic formation with fluid-fluid levels in extracranial head and neck tumors.